Systemic Risk Assessment in Low Income Countries : Balancing Financial Stability and Development - Marchettini, Daniela (IMF Working Papers; Working Paper ;, 2015)
We propose a toolkit for the assessment of systemic risk buildup in low income countries. We show that, due to non-linearity in the relationship between credit and financial stability, the assessment should be conducted with different tools at different stages of financial development. In particular, when the level of financial depth is low, traditional leading indicators of banking crises have poor predictive performance and the analysis should be based on indicators that account for financial deepening while taking into consideration countries' structural limits. By using this framework, we provide a preliminary assessment of systemic risk buildup in individual SSA countries.